Systematic Property Registration : Risks and Remedies - Lamb, Tony (World Bank, Washington, DC, 2017)
This paper looks at a variety of technical issues, challenges, and problems that arise during systematic first registration programs, their causes and what can be done to deal with them. Its aim is to provide practical advice to those who are designing or engaged in first registration programs that use the systematic adjudication approach and also those who supervise such programs so that the issues covered in this paper can be eliminated or their negative impact reduced. The paper draws primarily from the land registration experience in the Europe and Central Asia region and uses examples from that region, but as relevant, examples from elsewhere are included. This paper is divided into four parts: (1) design, (2) implementation, (3) owners, and (4) legal issues.